Isolation of Plasma Membranes from Corn Roots by Sucrose Density Gradient Centrifugation: An Anomalous Effect of Ficoll - Leonard, Robert T. (1976)
An investigation was conducted into the isolation of plasma membrane vesicles from primary roots of corn (Zea mays L., WF9 × M14) by sucrose density gradient centrifugation. Identification of plasma membranes in cell fractions was by specific staining with the periodic-chromic-phosphotungstic acid procedure. Plasma membrane vesicles were rich in K(+)-stimulated ATPase activity at pH 6.5, and equilibrated in linear gradients of sucrose at a peak density of about 1.165 g/cc. It was necessary to remove mitochondria (equilibrium density of 1.18 g/cc) from the homogenate before density gradient centrifugation to minimize mitochondrial contamination of the plasma membrane fraction. Endoplasmic reticulum (NADH-cytochrome c reductase) and Golgi apparatus (latent IDPase) had equilibrium densities in sucrose of about 1.10 g/cc and 1.12 to 1.15 g/cc, respectively. A correlation (r = 0.975) was observed between K(+)-stimulated ATPase activity at pH 6.5 and the content of plasma membranes in various cell fractions. ATPase activity at pH 9 and cytochrome c oxidase activity were also correlated. A major peak of ATPase activity at pH 6.5 was observed at low density in Ficoll after nonequilibrium centrifugation in a combination Ficoll-sucrose gradient. Twenty to forty percent of the vesicles in this ATPase fraction stained positively for plasma membranes, and with equilibrium centrifugation the major portion of the ATPase activity shifted to densities in sucrose which were characteristic of plasma membranes. All major vesicular ATPase activities observed in Ficoll or sucrose contained substantial amounts of plasma membranes. For unknown reasons, mitochondria and plasma membranes equilibrated over a broader density range and at lower peak densities in sucrose as a result of equilibrium centrifugation through Ficoll.